Kahoot-Based Team Quiz Strategy to Improve Elementary School Students’ Mathematics Learning Activity and Outcomes - Inda Lesmana; Siti Aisyah; Adriantoni Adriantoni (Journal of Educational Sciences, 2026)
This research aims to improve the activity and learning outcomes of fifth-grade students at SDN 23 Tanjung Gadang in mathematics through the implementation of the Team Quiz strategy supported by Kahoot. The study used the Classroom Action Research (CAR) method with the Kemmis and Taggart model, conducted in two cycles of two meetings each. The subjects consisted of 17 students. Instruments included observation sheets of student activity, learning achievement tests, and documentation. In the pre-cycle stage, the average student achievement was only 63%, with five students reaching mastery. After the action in Cycle I, improvements appeared: the average score increased to 65% in the first meeting and 75% in the second, with nine and eleven students achieving mastery. More significant progress occurred in Cycle II, where the average scores rose to 79% in the first meeting and 85% in the second, with sixteen students meeting mastery. Observation results showed that initially passive behaviors changed into active and enthusiastic participation in discussions, questioning, and Kahoot-based quizzes. The classroom atmosphere became more lively, competitive, and enjoyable. The study concludes that the Team Quiz strategy using Kahoot effectively enhances motivation, cooperation, and mathematics learning outcomes.